Behaviour and decision making of Czech consumers when buying beverages - M. Foret; P. Procházka (Agricultural Economics (AGRICECON), 2006)
The article deals with the problem of analysis of the factors that influence the behaviour and decision-making of consumers when buying beverages. The analysis was based on data about consumer behaviour obtained within the period of 1993-2004. The secondary analysis involved data collected within the framework of a marketing research project SHOPPING MONITOR performed by the marketing agencies INCOMA Research and GfK Prague in years 1999-2002. Based on the results obtained, it was concluded that hypermarkets were dominating not only as a place of purchasing foodstuffs in general but also as a leading outlet for sale of beverages. Czech consumers preferred Czech brands of beverages and there was a new trend in increasing purchases of tea, juices and mineral water on the one hand and coffee and wine on the other. This indicates a change in consumption habits and reflects an interest in a healthier life style.